2000
DOI: 10.1021/jm001008m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Steroidal Oxime Inhibitors of P450 17 (17α-Hydroxylase/C17−20-Lyase) and 5α-Reductase Types 1 and 2

Abstract: 17 alpha-Hydroxylase/C17-20-lyase (P450 17, CYP 17) and 5 alpha-reductase are the key enzymes in androgen biosynthesis and targets for the treatment of prostate cancer and benign prostatic hyperplasia. In the search of inhibitors for both enzymes, 23 pregnenolone- or progesterone-based steroids were synthesized bearing an oxime group connected directly or via a spacer to the steroidal D-ring. Tested for inhibition of human and rat P450 17, some pregnenolone (9, 11, 14) and a series of progesterone compounds (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 64 publications
(131 reference statements)
3
38
0
Order By: Relevance
“…androgens). Competitive P450c17 inhibitors with K I values in the 3-9 nM range have been reported by Hartmann et al (62,63), and Ideyama et al (64) have reported that the nonsteroidal compound 2-(1H-imidazol-4-ylmethyl)-9H-carbazole (named "YM116") competitively inhibits the 17,20-lyase activity with a K I of 0.38 nM. Since prostate cancers typically show androgen-dependent growth, inhibitors for P450c17 may represent promising therapeutic agents for prostate cancer.…”
Section: Discussionsupporting
confidence: 52%
“…androgens). Competitive P450c17 inhibitors with K I values in the 3-9 nM range have been reported by Hartmann et al (62,63), and Ideyama et al (64) have reported that the nonsteroidal compound 2-(1H-imidazol-4-ylmethyl)-9H-carbazole (named "YM116") competitively inhibits the 17,20-lyase activity with a K I of 0.38 nM. Since prostate cancers typically show androgen-dependent growth, inhibitors for P450c17 may represent promising therapeutic agents for prostate cancer.…”
Section: Discussionsupporting
confidence: 52%
“…As compound 1 has been shown to be a strong inhibitor of P450 17 [8] , the low activity of 2 (and 3) cannot be due to steric reasons. It is more likely that the hydroxamate group is a low activity monodentate ligand compared to the oxime group, which might be due to the electron withdrawing effect of the carbonyl group or to an inappropriate state of the tautomeric equilibrium (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the oxime group has been found to be appropriate for the design of potent steroidal inhibitors [8,2] (as an example see compound 1, Chart 1). Structurally related to oximes are hydroxamic acids which exist in solution in two tautomeric forms (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…2)-based steroids bearing an oxime group connected directly or via a spacer to the steroidal D ring, where the oxime group is capable to form a coordinate bond with heme iron of enzyme (Hartmann et al, 2000). On the other hand, progesterone esters (3a, 3b) (Fig.…”
Section: Introductionmentioning
confidence: 99%